Applications of Big Data and Artificial Intelligence in Smart Energy Systems Volume 1 Smart Energy System: Design and Its State-Of-the Art Technologies. - Nagpal, Neelu; Alhelou, Hassan Haes, 1988-; Siano, Pierluigi; Sanjeevikumar, Padmanaban, 1978-; Lakshmi, D. (River Publishers, 2023)
This book covers the applications of various big data analytics, artificial intelligence, and machine learning technologies in smart grids for demand prediction, decision-making processes, policy, and energy management.
Description based upon print version of record.
4.1.2.3: Gaussian mixture model (GMM)
Keywords: Smart power grids.; Big data -- Industrial applications.; Artificial intelligence -- Industrial applications.; elektronické knihy; electronic books